2020
DOI: 10.1002/agj2.20312
|View full text |Cite
|
Sign up to set email alerts
|

Alfalfa establishment by interseeding with silage corn projected to increase profitability of corn silage–alfalfa rotations

Abstract: The USDA prohibits discrimination in all its programs and activities on the basis of race, color, national origin, age, disability, and where applicable, sex, marital status, family status, parental status, religion, sexual orientation, genetic information, political beliefs, reprisal, or because all or part of an individual's income is derived from any public assistance program (not all prohibited bases apply to all programs.). USDA is an equal opportunity provider and employer. Mention of commercial products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 25 publications
1
27
1
Order By: Relevance
“…However, the study in Wisconsin was done at lower maize grain prices than in our study, which was calculated with a grain price of $177 Mg −1 . Thus, the net return of silage maize rotations were similar to those calculated for a two-year sequence of silage maize ($379 Mg −1 ) The alfalfa forage yield used by Osterholz et al [17] in the economic analysis were very similar to those used in our analysis. Osterholz et al [17] used alfalfa forage yields of 11.4 Mg ha −1 and 5.8 Mg ha −1 for alfalfa coming from intercropping with maize in the previous year and spring-seeded alfalfa, respectively.…”
Section: Economic Analysissupporting
confidence: 82%
See 4 more Smart Citations
“…However, the study in Wisconsin was done at lower maize grain prices than in our study, which was calculated with a grain price of $177 Mg −1 . Thus, the net return of silage maize rotations were similar to those calculated for a two-year sequence of silage maize ($379 Mg −1 ) The alfalfa forage yield used by Osterholz et al [17] in the economic analysis were very similar to those used in our analysis. Osterholz et al [17] used alfalfa forage yields of 11.4 Mg ha −1 and 5.8 Mg ha −1 for alfalfa coming from intercropping with maize in the previous year and spring-seeded alfalfa, respectively.…”
Section: Economic Analysissupporting
confidence: 82%
“…Silage yield losses between treatments were not observed in this study. However, similar research has shown that intercropping maize with alfalfa usually has a yield penalty of up to 30% [17]. Thus, we included a sensitivity analysis of net returns with a price of $41.1 Mg −1 silage maize at 65% moisture, and $166 Mg −1 for 0 to 30% silage yield losses due to intercropping.…”
Section: Economic Analysismentioning
confidence: 99%
See 3 more Smart Citations